Dietary Bacillus subtilis improves early post-mortem lamb tenderness via the AMPK-YAP-autophagy axis - Yuhan Zhang; Junkang Xie; Guangxin Li; Mengqi Zhang; Lin Su; Ye Jin; Yueying Guo (Small Ruminant Research, 2026)

Root exudates recruit microbial allies to override their own mobilization effects for cadmium immobilization in intercropped rice - Ye Li; Jie Hou; Mengqi Liu; Hongan Chen; Xinyi Wang; Peizhe Sun; Lin Zhao; Yanpo Yao; Zhaolin Du; Yi An (Journal of Hazardous Materials, 2026)

Construction and immunogenicity evaluation of avian Escherichia coli-derived bacterial biomimetic vesicles displaying H9 subtype avian influenza virus HA1 protein - Yue Li; Yuji Quan; Keji Quan; Mengqi Lin; Peng Chen; Xiangkai Zhuge; Tao Qin; Sujuan Chen; Yuncong Yin; Daxin Peng (Veterinary Microbiology, 2026)

High-pressure disruption for efficient protein extraction from Chlorella pyrenoidosa: comparative insights with conventional methods - Chen Zhang; Mengqi Nong; Yu Luo; Marco Marcucci; Yihuan Li; Zexin Lin (Innovative Food Science & Emerging Technologies, 2026)

Microfluidic-based magnetic microspheres for targeted delivery of curcumin nanoparticles in gastroesophageal reflux disease therapy - Haoyao Jiang; Zhonglin Fang; Han Lin; Di Xu; Wanqian Xu; Mengqi Han; Luoran Shang; Ye Zhao; Teng Ma; Di Ge (Chemical Engineering Journal, 2026)

Rhubarb-derived extracellular vesicles co-delivered with dexamethasone via multi-layered assembly nanostrategy for targeted ulcerative colitis therapy - Kun Wang; Mengqi Shen; Xu Luo; Lin Li; Ming Wu; Xiaotong Zhang; Huilin Zhu; Qian Du (Chemical Engineering Journal, 2026)

Evaluating the Shanghai Typhoon Model against State-of-the-Art Machine-Learning Weather Prediction Models: A Case Study for Typhoon Danas (2025) - Zeyi Niu; Wei Huang; Yuhua Yang; Mengqi Yang; Lin Deng; Haibo Wang; Hong Li; Xu Zhang (Advances in Atmospheric Sciences, 2026)

Coral-inspired in situ immobilized lipase on covalent organic framework for efficient synthesis of flavor esters - Shengli Ding; Mengqi Wang; Guiqing Lin; Yanrong Song; Ji Zhang; Yufei Zhang; Mingming Zheng (Food Chemistry, 2026)

Genetically Modified Primate Models for Brain Disorder Research - Yi Yang; Jianbang Lin; Mengqi Li; Lixin Yang; Zhonghua Lu; Ting Yan (Neuroscience Bulletin, 2026)

Characterization and structural analysis of a novel glucurono-xylanase from Chaetomium fimeti and its potential application in pear juice clarification - Xingyu Liu; Lin Han; Mengqi Liu; Jinglei Wu; Dandan Zhao; Huan Rao; Xia Zhao; Xuechao Zheng; Jianxiong Hao; Xueqiang Liu (Food Research International, 2026)

A meta-plasmonic biosensor for minimal protein interference profiling of serum extracellular vesicles enables high-specific discrimination of liver cancer subtypes - Jiaheng Zhu; Shaowei Lin; Baichang Deng; Jiaqing Shen; Lihuang Zeng; Qiang Niu; Tianhao Huang; Xinyue Huang; Mengqi Jiang; Wei Chen; Yinong Xie; Annuo Chen; et al. (Chemical Engineering Journal, 2026)

Multiomics and machine learning unveil root exudate-microbiota interactions for cadmium control in rice - Ye Li; Jie Hou; Mengqi Liu; Zhaolin Du; Hongan Chen; Guofei Liu; Yajun Wang; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Environmental Management, 2025)

A systematic analysis of the sensory qualities of Asparagus cochinchinensis (lour.) Merr. From the four major production areas in China: Sensory characteristics, key flavor substances, and molecular mechanisms of flavor formation - Jingping Zhong; Shuyu Deng; Mengqi Li; Honglin Yin; Xinming Chen; Zhiyan Deng; Xiaoming Bao; Qingchu Tan; Junzhi Lin; Dingkun Zhang; Gang Shen; Li Han; et al. (Food Chemistry, 2025)

Long-term tea cultivation degrades soil health: Insights from microbial structure and function in tea gardens - Xinyi Chen; Mengqi Lin; Zhenghao Wu; Lei Yu; Qingxue Guo (Soil Ecology Letters, 2025)

Ultimate strength of bamboo scrimber-concrete composite beams with UHPC and ECC: Experimental investigation, finite element simulation and prediction model - Mengqi Cao; Youzhu Lin; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Erianin reverses 5-FU resistance by targeting CALM1/CAMKK2 and activating autophagy in colorectal cancer - Fangyuan Zhou; Luorui Shang; Jinxiao Li; Mengqi Zhang; Shuhan Wang; Yuju Cai; Qifeng Lin; Haiyang Gao; Shenglan Yang (Chemico-Biological Interactions, 2025)

A comprehensive perspective on intestinal health, physiological status, and growth performance of Larimichthys crocea with different stocking densities in recirculating aquaculture systems - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture International, 2025)

A machine learning and counterfactual reasoning-integrated decision framework for cadmium remediation: Predictive optimization and cost-benefit analysis driven by iron plaque regulation - Ye Li; Jie Hou; Mengqi Liu; Ruilin Li; Zhaolin Du; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Hazardous Materials, 2025)

Construction of lithium single-ion polymer electrolytes with octuple hydrogen bonds: Realizing interface adaptation for all-solid-state lithium metal batteries - Tianwei Hao; Yujian Shen; Chaolong Yang; Mengqi Ma; Wenhong Ruan; MuSong Lin (Chemical Engineering Journal, 2025)

Enhanced detection of crowded NMR peaks using longitudinal multi-spin order for chemical analysis - Yulan Lin; Wei Liang; Longxiang Chen; Chaoxing Liu; Mengqi Cui; Hongrong Chen; Zhong Chen (Analytica Chimica Acta, 2025)

Effects of exercise intensity on large yellow croaker (Larimichthys crocea): A comprehensive analysis of growth, physiology, muscle fiber structure, and gut health - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Jie Ding; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Synergistic triboelectric and antibacterial properties in biodegradable nanofiber membranes for air filtration - Yi Liu; Shuai Zheng; Mengqi Wang; Xiaoyu Zhang; Fei Wang; Jun Yu; Xiaodong Hu; Jinyou Lin; Yuqing Liu (Journal of Hazardous Materials, 2025)

Mass and heat balance of sea ice during the thaw-freezing transition in the Pacific sector of Arctic Ocean derived from the buoy measurements in 2018 - Mengqi Wu; Ruibo Lei; Bin Cheng; Long Lin; Na Li; Xiaomin Chang (Acta Oceanologica Sinica, 2025)

Photothermal-thermoelectric synergy coupling localized surface plasmon resonance for enhanced flexible photoelectrochemical sensor performance - Mengqi Chen; Hui Tian; Ling Qi; Yuying Zhang; Hongmei Yang; Shenguang Ge; Lina Zhang; Yan Zhang; Lin Li; Kang Cui; Jinghua Yu (Chemical Engineering Journal, 2025)

Mechanisms of energy efficiency of supply momentum-driven stratified thermal environment with exhaust and return vents isolated by supply vent - Xia Zhang; Mengqi Jiang; Longxia Ma; Sheng Zhang; Zhaosong Fang; Yongjun Sun; Zhang Lin (Building and Environment, 2025)

Differences in willingness to pay for various types of carbon-labeled products: A dynamic perspective - Mengqi Yang; Boqiang Lin (Journal of Environmental Management, 2024)

Comparison and identification of aroma components in 21 kinds of frankincense with variety and region based on the odor intensity characteristic spectrum constructed by HS–SPME–GC–MS combined with E-nose - Xinming Chen; Dandan Yang; Lin Huang; Mengqi Li; Jihai Gao; Can Liu; Xiaoming Bao; Zhizhi Huang; Jinhui Yang; Haozhou Huang; Dingkun Zhang; Runchun Xu (Food Research International, 2024)

Electronic effect in bromide-modified noble metal catalysts promotes highly stable and selective hydrogenation - Xintai Chen; Mengqi Yang; Qiying Liu; Xiaoling Mou; Linbin Ying; Yu Meng; Ronghe Lin; Yunjie Ding (Chemical Engineering Journal, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Tetrabromobisphenol A exerts thyroid disrupting effects but has little overt impact on postnatal brain development and neurobehaviors in mice - Shilin Song; Yuanyuan Li; Lin Lv; Mengqi Dong; Zhanfen Qin (Journal of Environmental Sciences, 2024)

Making policies more effective: The differentiated impact of work-family conflict on environmental public participation - Mengqi Yang; Boqiang Lin (Environmental Science & Policy, 2024)

Optical investigation on effects of diesel injection strategy on ammonia/diesel dual fuel combustion characteristics and flame development - Wenpeng Zeng; Wanchen Sun; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu (Fuel, 2024)

Changes in consumer satisfaction with electric vehicle charging infrastructure: Evidence from two cross-sectional surveys in 2019 and 2023 - Boqiang Lin; Mengqi Yang (Energy Policy, 2024)

Two new glycosides from Stachys geobombycis C.Y.Wu - Mengqi Yan; Xiaoya Xian; Lin Liang; Xianli Zhou; Weiquan Xie; Chengqin Liang (Natural Product Research, 2024)

Optical diagnostic study of internal and external EGR combined with oxygenated fuels of n-butanol, PODE3 and DMC to optimize the combustion process of FT synthetic diesel - Wanchen Sun; Genan Zhu; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Wenpeng Zeng; Xin Zhang; Mengqi Jiang; Changyou Yu (Fuel, 2024)

East meets west in alcoholic beverages: Flavor comparison, microbial metabolism and health effects - Mengwei Lin; Bingyan Yang; Mengqi Dai; Youqiang Xu; Xiuting Li; Baoguo Sun (Food Bioscience, 2023)

Unlocking the potential of resuscitation-promoting factor for enhancing anaerobic microbial dechlorination of polychlorinated biphenyls - Zhen Han; Aiqin Hou; Xiaolin Cai; Mengqi Xie; Faqian Sun; Chaofeng Shen; Hongjun Lin; Haiying Yu; Xiaomei Su (Science of The Total Environment, 2023)

Numerical study of injection strategies for marine methanol/diesel direct dual fuel stratification engine - Wanchen Sun; Mengqi Jiang; Liang Guo; Hao Zhang; Zhiqin Jia; Zhenshan Qin; Wenpeng Zeng; Shaodian Lin; Genan Zhu; Shenyue Ji; Yimo Zhu (Journal of Cleaner Production, 2023)

An optical study of the combustion and flame development of ammonia-diesel dual-fuel engine based on flame chemiluminescence - Wanchen Sun; Wenpeng Zeng; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu; Fei Wu (Fuel, 2023)

The intricate relationship between autoimmunity disease and neutrophils death patterns: a love-hate story - Ziwei Zhang; Lin Jin; Lianghu Liu; Mengqi Zhou; Xianzheng Zhang; Lingling Zhang (Apoptosis, 2023)

The decadal abrupt change in the global land vapor pressure deficit - Mengqi Cheng; Zhiyan Zuo; Zouxing Lin; Qinglong You; Huan Wang (Science China Earth Sciences, 2023)

Numerical investigation of submerged flexible vegetation dynamics and wave attenuation under combined waves and following currents - Kai Yin; Ming Lin; Sudong Xu; Jianxin Hao; Liuyan Mao; Mengqi Li (Ocean Engineering, 2023)

Succession and environmental response of sediment bacterial communities in the Liao River Estuary at the centenary scale - Zining Guo; Yan Li; Mengqi Shao; Tongxin Sun; Mengping Lin; Tie Zhang; Ke Hu; Hongchen Jiang; Xiangyu Guan (Marine Environmental Research, 2023)

Experimental Study on the Efficiency of Dynamic Marine Thermal Energy Generator Based on Phase Change Compensation - Ruichun Dong; Xu Lin; Jie Liu; Mengqi Hu; Zezheng Liu; Jingze Yang; Libin Du (Journal of Marine Science and Engineering, 2023)
Miniaturized detection devices in the ocean generally experience problems such as short endurance and unreliable power supplies. This article aimed to develop a dynamic ocean temperature difference energy collection device to capture ocean temperature difference energy and provide objective electricity for stable detection devices. The main focus was to conduct experimental research on the effectiveness of a dynamic ocean temperature difference energy power generation device. During the research process, the fact that ammonia gas in a working fluid is easy to liquefy and vaporize was utilized. By utilizing the increase in seawater temperature during the floating process of the device, it vaporized and drove the turbine to rotate for power generation. In the structural design, multiple sets of small air chambers were creatively proposed, which could effectively control the air pressure and improve the stability of the airflow. By charging the airflow to impact the turbine, multiple sets of power generation fans were used to form a stable current. Further, the buoyancy of the device could be changed by adding phase change materials between the air chamber and the device shell, and the temperature difference between the two ends of the phase change materials could be used to change the electron density of the material to form a weak current. In this experimental study, concepts such as the structural design of multiple small gas chambers, miniaturization of energy collection devices, compensation power generation of phase change materials, and application scenarios of devices combined with Argo buoys were all proposed for the first time. The results of this experimental study indicate that the overall power generation of the device is about 2A, and its maximum output power amplitude is about 22 W. The cyclic thermal efficiency of the power generation device can be increased from +0.19% to +0.88%. The development of this thermoelectric power generation device can provide a considerable stable power supply for ocean observation devices, especially the buoy device represented by Argo, which can extend the endurance of deep-sea exploration devices.

Measuring segregation in fluidized bed with magnetizable and nonmagnetizable particles based on magnetic permeability - Quanhong Zhu; Qiang Zhang; Peiyi Yang; Hengjun Gai; Mengqi Lin; Hongbing Song; Meng Xiao; Tingting Huang (Fuel, 2023)

Effects of light on growth, feeding rate, digestion, and antioxidation in juvenile razor clams Sinonovacula constricta - Mengqi Zhang; Fei Kong; Bin Ma; Deshui Chen; Zhaoshou Ran; Shuonan Ma; Kai Liao; Jiayi Cao; Lin Zhang; Xiaojun Yan; Jilin Xu (Aquaculture, 2023)

Dual-dense gas-solid circulating fluidized bed reactor - Hengjun Gai; Peiyi Yang; Qiang Zhang; Mengqi Lin; Hongbing Song; Meng Xiao; Tingting Huang; Quanhong Zhu (Fuel, 2023)

Choosing the right policy: Factors influencing the preferences of consumption-side personal carbon reduction policies - Boqiang Lin; Mengqi Yang (Journal of Environmental Management, 2023)

Microarray analysis of mRNA expression profiles in liver of ob/ob mice with real-time atmospheric PM2.5 exposure - Lisen Lin; Li Tian; Tianyu Li; Mengqi Sun; Junchao Duan; Yang Yu; Zhiwei Sun (Environmental Science and Pollution Research, 2022)

Identification of serum metabolites enhancing inflammatory responses in COVID-19 - Chen-Song Zhang; Bingchang Zhang; Mengqi Li; Xiaoyan Wei; Kai Gong; Zhiyong Li; Xiangyang Yao; Jianfeng Wu; Cixiong Zhang; Mingxia Zhu; Lei Zhang; Xiufeng Sun; et al. (Science China Life Sciences, 2022)

The Chinese species of skipper butterflies in the tribe Tagiadini Mabille, 1878 (Lepidoptera: Hesperiidae): insights from phylogeny, hostplants, and biogeography - Li Shen; Jianqing Zhu; Yuxiang Lin; Jie Fang; Yongqiang Wang; Liying Tang; Qinghao Zhao; Mengqi Xiao; Feiyu Duan; Qunxiu Liu; Weidong Yu; Weibin Jiang (Organisms Diversity & Evolution, 2022)

Effects of ambient air pollution on glycosylated hemoglobin: a systematic review and meta-analysis - Li Tian; Mengqi Sun; Lisen Lin; Yan Wang; Yang Yu; Junchao Duan; Zhiwei Sun (Environmental Science and Pollution Research, 2022)

Production of purple Ma bamboo (Dendrocalamus latiflorus Munro) with enhanced drought and cold stress tolerance by engineering anthocyanin biosynthesis - Mengqi Xiang; WenSha Ding; Chu Wu; Wenjia Wang; Shanwen Ye; Changyang Cai; Xin Hu; Nannan Wang; Weiyuan Bai; Xiaoshan Tang; Caiping Zhu; Xiaomin Yu; et al. (Planta, 2021)

Association of Circulating and Aortic Zinc and Copper Levels with Clinical Abdominal Aortic Aneurysm: a Meta-analysis - Tingting Chen; Hongliang Zhang; Yang Zhang; Mengqi Yang; Juntao Wu; Minjun Yang; Jiangbo Lin; Weixu Gao; Lijiang Tang; Baohui Xu; Jianjun Jiang; Xiaofeng Chen (Biological Trace Element Research, 2021)

A minor QTL, SG3, encoding an R2R3-MYB protein, negatively controls grain length in rice - Qiuping Li; Li Lu; Haiyang Liu; Xufeng Bai; Xin Zhou; Bi Wu; Mengqi Yuan; Lin Yang; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

The degradation of BPA on enhanced heterogeneous photo-Fenton system using EDDS and different nanosized hematite - Xiaoqing Feng; Mengqi Luo; Wenyu Huang; Ying Huang; Hongjie Xie; Zisong Xu; Jian Zhang; Wei Luo; Shuangfei Wang; Hongfei Lin (Environmental Science and Pollution Research, 2020)